A Physical Layer Security Technique for NOMA Systems with MIMO SC-FDE Schemes - João Madeira (Electronics, 2020)
Current wireless communication systems employ Multi-Input, Multi-Output (MIMO) techniques to increase spectral efficiency, at the cost of higher hardware complexity. Most of these systems continue to employ traditional Orthogonal Multiple Access (OMA) schemes, which are suboptimal when compared to Non-Orthogonal Multiple Access (NOMA) schemes. By combining NOMA with MIMO, it is possible to achieve higher spectral efficiencies. However, security in NOMA-MIMO systems remains a problem. In this paper, we study the physical layer security issues of a power based NOMA-MIMO system with a Singular Value Decomposition (SVD) scheme, employed along with Single Carrier with Frequency Domain Equalization (SC-FDE) techniques. We consider a scenario where there is an unintended eavesdropper attempting to listen to the messages being exchanged. It is shown that the higher the channel estimate correlation between transmitter and receiver, the higher the secrecy rate, particularly for a scenario where there is a Line-Of-Sight (LOS) between all users. Therefore, power based NOMA MIMO-SVD schemes, combined with SC-FDE, can be considered efficient options for highly secure MIMO communications.